Uji Organoleptik Susu Kambing Pasteurisasi dengan Penambahan Ekstrak Daun Ubi Jalar Ungu - Fauzi, Muhamad; Sihite, Mikael; Farida, Farida (Unpad Press, 2024)
Goat milk have disadvantage of short shelf life and prengus smell. The short shelf life can be handled by pasteurization and the smell of prengus can be reduced by adding ingredients that contain antioxidants, one of which is purple sweet potato leaves. The aim of this study was to examine the organoleptic quality of pasteurized goat milk with the addition of purple sweet potato leaf extract. The experimental design used was a completely randomized design with four different concentrations of purple sweet potato leaf extract (0%, 2%, 4%, and 6%) with five replications. Variables observed were color, smell, langu (unpleasant) taste, prengus taste, texture, and preferences. Data were analyzed using analysis of variance (ANOVA) at the 5% level. Significantly different data were further tested using Duncan's Multiple Range Test (DMRT). Results showed that the addition of purple sweet potato leaf extract at a concentration of 2-6% had an effect (P<0.05) on color, smell, langu (unpleasant) taste, texture, and preferences but had no effect on the prengus taste. The most purplish color is obtained at a concentration of 6%. The least prengus smell is obtained at a concentration of 4%. The lowest langu (unpleasant) taste, the most characteristic texture of milk, and the highest preference is obtained at a concentration of 0%.